Determining the mechanism of pulsatilla decoction for treating gastric cancer: a network pharmacology-based study - Huang, Siqi; Qu, Manying; Chen, Xiaowu; Yu, Shaochen; Kong, Fanhua (Frontiers in Oncology, 2023)
Background and aim: Gastric cancer (GC) is a prevalent malignancy worldwide. Pulsatilla decoction (PD), a traditional Chinese medicine formula, can treat inflammatory bowel disease and cancers. In this study, we explored the bioactive components, potential targets and molecular mechanisms of PD in the treatment of GC. Methods: We conducted a thorough search of online databases to gather gene data, active components, and potential target genes associated with the development of gastric cancer. Subsequently, we conducted bioinformatics analysis utilizing protein-protein interaction (PPI), network construction, and Kyoto Encyclopedia of Genes and Genomes (KEGG) to identify potential anticancer components and therapeutic targets of PD. Finally, the efficacy of PD in treating GC was further validated through in vitro experiments. Results: Network pharmacological analysis identified 346 compounds and 180 potential target genes associated with the impact of PD on GC. The inhibitory effect of PD on GC may be mediated through modulation of key targets such as PI3K, AKT, NF-κB, FOS, NFKBIA and others. KEGG analysis showed that PD mainly exerted its effect on GC through the PI3K-AKT, IL-17, and TNF signaling pathways. Cell viability and cell cycle experiments showed that PD could significantly inhibit proliferation and kill GC cells. Moreover, PD primarily induces apoptosis in GC cells. Western blotting analysis confirmed that the PI3K-AKT, IL-17, and TNF signaling pathways are the main mechanisms by which PD exerts its cytotoxic effects on GC cells. Conclusion: We have validated the molecular mechanism and potential therapeutic targets of PD in treating GC through network pharmacological analysis, thereby demonstrating its anti-cancer efficacy against GC.